Asymmetric dimethylarginine mediates oxidative stress and atrial remodeling in HL-1 cells - Yu, Chengyun; Zhang, Ming; Xia, Wei (Frontiers in Medicine, 2025)
IntroductionAtrial fibrillation (AF) is a common cardiac arrhythmia, and endothelial dysfunction and oxidative stress (OS) are key mechanisms promoting atrial remodeling. Asymmetric dimethylarginine (ADMA) inhibits nitric oxide synthase (NOS) but its role in AF-related atrial remodeling remains unclear.MethodsMouse atrial myocyte HL-1 cells were treated with ADMA, H2O2, N-acetylcysteine (NAC), or their combinations. Cell viability, reactive oxygen species (ROS) levels, and TGF-β1 expression were detected using CCK-8, flow cytometry, fluorescence microscopy, and Western blot. A clinical cohort study included 60 AF patients and 30 controls to measure serum ADMA, TGF-β1, and NO levels.ResultsADMA (30 μM) significantly increased ROS generation and upregulated p47phox and TGF-β1 expression in HL-1 cells, which was reversed by NAC. AF patients had higher serum ADMA and TGF-β1 levels and lower NO levels than controls (P<0.01).DiscussionADMA may induce TGF-β1 expression by enhancing NOX-ROS levels, leading to myocardial oxidative damage and atrial remodeling, which provides new insights into AF pathophysiology.